The Extent of Accounting Graduates Knowledge Competence in Activity Based Costing Systems that Necessary To Meet the Needs of Industrial Sector in Jordan: Case Study of Jordanian Universities - Weshah, Sulaiman; Shanti, Ayman; Owais, Walid; Alnajdawi, Akram (The Arab Journal of Administration, 2021)
This study aimed to clarify level of Jordanian universities student’s knowledge in Activity Based Costing (ABC). Also, to find out if accounting bachelor students at Jordanian universities are dealing with the subject of ABC as a cost accounting system through their learning of cost accounting or related subjects. After study problem determined, an appropriate hypothesis was developed to achieve study objectives, a questionnaire was developed as a tool for collecting data and information related to the study. It was distributed to public universities such as Jordan, Al-Bayt, Hashemite, Yarmouk and Al-Balqa universities. As for private universities, they were represented by Al-Ahliyya Amman University, Applied Sciences, Petra, Philadelphia, and Zarqa-Al-Ahliyya as a field study sample. After using study tool and data collection, it was processed by using SPSS statistical program according to the purposes of the study based on the methods of measuring variables so that the statistical methods that fit the study hypotheses and variables were employed. The study found several conclusions, the most important of which is that the rate of undergraduate students’ knowledge of (ABC) system is generally low and accounting lecturers for undergraduate students in Jordanian universities are rarely deeply explaining the subject (ABC) system. The study recommended reviewing the proposed plans for cost accounting and managerial accounting so that the subject of the ABC system is discussed in more detail while it is implementation is spreading through practical field.